The effectiveness of acceptance and commitment therapy on emotional regulation and disease perception in women with irritable bowel syndrome - Moghtadaei, Kamal; Ebrahimi, Amrolah; Haghayegh, Seyed Abbas; Rezaie Jamalouei, Hasan; Adibi, Peyman (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The aim of this study was to evaluate the effectiveness of acceptance and commitment therapy on emotional regulation and perception of the disease in women with irritable bowel syndrome. Methods: The quasi-experimental research method was a pretest-posttest design with a control group with follow-up. The statistical population of this study was all female patients with irritable bowel syndrome in Isfahan in 2018 who were selected by available sampling method, 30 patients were selected and randomly divided into an intervention group by acceptance and commitment therapy and a control group that finally, after falling, 28 remained (experimental group 13 and control group 15). The experimental group underwent 8 90-minute sessions of acceptance and commitment according to the protocol of Hayes, Orsillo, & Roemer (2010) and the control group remained on the waiting list. Data were collected based on the Disease Perception Questionnaire (Broadbent et al., 2002) and the Emotion Regulation Questionnaire (Gross and John, 2003) and repeated measures analysis of variance was used using SPSS software. Results: The results showed that the method of acceptance and commitment treatment had an effect on emotional regulation (F=24.09, P